Software test attacks to break mobile and embedded devices - Hagar, Jon Duncan (CRC Press, 2014)
he book guides you step by step starting with the basics. It explains patterns and techniques ranging from simple mind mapping to sophisticated test labs. For traditional testers moving into the mobile and embedded area, the book bridges the gap between IT and mobile/embedded system testing. It illustrates how to apply both traditional and new approaches. For those working with mobile/embedded systems without an extensive background in testing, the book brings together testing ideas, techniques, and solutions that are immediately applicable to testing smart and mobile devices.